Dragons. Dawn of the dragon racers. [videorecording (DVD)] - Baruchel, Jay, 1982-; Ferrera, America, 1984-; Mintz-Plasse, Christopher, 1989-; Cowell, Cressida (Twentieth Century Fox Home Entertainment, 2014)
Hiccup, Toothless, and their fearless friends are flying higher than ever in an all-new adventure - and Berk will never be the same! When a hunt for lost sheep turns into a fierce, fun-filled competition, the villagers will defy tradition to prove who is the fastest in the island's first Dragon Racing Championship.